From sin to amazing grace : discovering the queer Christ - Cheng, Patrick S. (New York : Seabury Books, 2012)
This book provides a unique synthesis of liberation, queer and postcolonial theologians over the last few decades within a unified theological framework. It Will advance the inclusion of LGBT people within church and society. This book is a useful resource for all people who struggle to make sense of the traditional Christian doctrines of sin and grace in the 21st century. Throughout the history of Christianity, lesbian, gay, bisexual and transgender ("LGBT" or "queer") people have been condemned as unrepentant sinners who are in dire need of God's saving grace. As a result of this condemnation, LGBT people have been subjected to great spiritual, emotional and physical abuse and violence. This issue has taken on a particular urgency in light of the horrific string of suicides over the last year of young LGBT people who were subjected to harassment and bullying by their classmates. Cheng argues that people need to be liberated from the traditional legal model of thinking about sin and grace as a violation of divine and natural laws in which grace is understood as the strength to refrain from violating such laws. Rather Cheng proposes a Christological model based upon the theologies of Irenaeus, Bonaventure and Barth, in which sin and grace are defined in terms of what God has done for us in Jesus Christ. - Publisher.
Why a book on sin and grace? -- A primer on sin and grace -- The crime-based model of sin and grace -- An alternative: the Christ-centered model of sin and grace -- Model one: the erotic Christ -- Model two: the out Christ -- Model three: the liberator Christ -- Model four: the transgressive Christ -- Model five: the self-loving Christ -- Model six: the interconnected Christ -- Model seven: the hybrid Christ.
Includes bibliographical references and index.
Keywords: Sin; Grace; Jesus Christ -- Persons and offices; Homosexuality -- Religious aspects -- Christianity